Minimum standard of treatment of aliens, fair and equitable treatment of foreign investors, customary international law and the Diallo case before the international court of justice (2021)
The Diallo Case before the International Court of Justice seems to offer a unique opportunity to declare both the minimum standard of treatment of aliens and the fair and equitable treatment standard as customary international law. This article analyzes the set of factors in play simultaneously in public international law and in international investment law that supports such expectations. However, the article also presents the other set of factors in these fields that does not provide strong support for the said hopes. The article concludes, first, that the Diallo Case could give the long-awaited clarification of the content of the minimum standard of treatment of aliens with regard to foreign investors; and, second, that it is unlikely that the fair and equitable treatment standard will end up receiving the official status of customary international law.